Insights into how predator diversity, population density and habitat type may affect defensive behaviour in a Mediterranean lizard. Issue 1 (2nd January 2019) - Savvides, Pantelis; Poliviou, Venetia; Stavrou, Maria; Sfenthourakis, Spyros; Pafilis, Panayiotis
Abstract : Various factors may alter anti-predatory responses among conspecifics. Here we assess some of these factors using three populations of a Mediterranean lizard ( Acanthodactylus schreiberi ) in Cyprus that differ in their habitat type, predator diversity and population density. We expected that predation would affect flight initiation distance (FID; the approach distance allowed to an observer before the lizard flees), escape distance (ED; the distance covered by the lizard from the point an escape attempt starts to the first place the lizard stops) and tail autotomy (autotomy rates, economy of autotomy, post-autotomy tail movement). We also predicted that juveniles, being more exposed to predators, would be more effective in their defensive responses. Our findings suggest that predation and population density appear to be associated with most autotomy traits but were not associated with FID and ED, which are better explained by refuge availability. The only ontogenetic difference was detected in the economy of autotomy: juveniles are more prone to autotomise, possibly because they do not experience such high costs as tailless adult individuals. Our results suggest that anti-predatory responses are influenced by a variety of factors. Unravelling the compound effects of all the factors involved should be the focus of future research.